Spin-glass dynamics in the presence of a magnetic field: exploration of microscopic properties. Issue 3 (8th March 2021) - Paga, I; Zhai, Q; Baity-Jesi, M; Calore, E; Cruz, A; Fernandez, L A; Gil-Narvion, J M; Gonzalez-Adalid Pemartin, I; Gordillo-Guerrero, A; Iñiguez, D; Maiorano, A; Marinari, E; et al.
Abstract: The synergy between experiment, theory, and simulations enables a microscopic analysis of spin-glass dynamics in a magnetic field in the vicinity of and below the spin-glass transition temperature T g . The spin-glass correlation length, ξ ( t, t w ; T ), is analysed both in experiments and in simulations in terms of the waiting time t w after the spin glass has been cooled down to a stabilised measuring temperature T < T g and of the time t after the magnetic field is changed. This correlation length is extracted experimentally for a CuMn 6 at. % single crystal, as well as for simulations on the Janus II special-purpose supercomputer, the latter with time and length scales comparable to experiment. The non-linear magnetic susceptibility is reported from experiment and simulations, using ξ ( t, t w ; T ) as the scaling variable. Previous experiments are reanalysed, and disagreements about the nature of the Zeeman energy are resolved. The growth of the spin-glass magnetisation in zero-field magnetisation experiments, M ZFC ( t, t w ; T ), is measured from simulations, verifying the scaling relationships in the dynamical or non-equilibrium regime. Our preliminary search for the de Almeida–Thouless line in D = 3 is discussed.